The Influence of Coretax, Tax Corner, and Tax Volunteers on Annual Personal Tax Return Reporting Compliance (a Study on Generation Z and Millennials in Lamongan) - MAIMUNAH, Handariyatul; DARMAYANTI, Novi; WAFA, Moh. Ali (Journal of Governance, Taxation and Auditing, 2025)
This study investigates the influence of tax education programs—Coretax, Pojok Pajak, and Relawan Pajak—on the compliance of Annual Personal Income Tax Return (SPT) reporting among Generation Z and Millennial taxpayers in Lamongan Regency. A descriptive quantitative approach was employed using a survey method, with data collected through both online and offline questionnaires. The target population included taxpayers aged 18–44 who possess a Taxpayer Identification Number (NPWP) and utilize the e-Filing system. A total of 106 respondents were selected using the Lemeshow formula and a purposive sampling technique. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. The findings reveal that Coretax and Relawan Pajak have a positive and significant impact on Annual Tax Return compliance, with path coefficients of 0.512 and 0.502, respectively (t-statistics > 1.96; p-values < 0.05). In contrast, Pojok Pajak did not exhibit a statistically significant effect. Demographically, the majority of respondents were female (63.21%), from Generation Z (69.81%), had a high school/vocational school education (56.60%), and were predominantly students (60.38%). The study concludes that Coretax and Relawan Pajak are effective tools for enhancing tax compliance among young taxpayers in the digital age. Accordingly, these programs should be strengthened and further developed as part of tax policy initiatives in Lamongan Regency to foster greater awareness and voluntary compliance among Millennials and Generation Z.